Computer modeling and verification of mechanical properties of metal-polymer composite materials used in the technological process of layer-by-layer growing of parts used in the technological process of layer-by-layer growing - Isametova М.; Absadykov, B.; Bazarbay, B.; Smailova, G.; Kalmaganbetov, S.; Deshevsky, N. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2022)
The article presents the results of computer modeling of the microstructure of a composite material consisting of a polyamide matrix and metal inclusions. The researched composition is one of the advanced trends in the production of materials for advanced MIM technologies. This paper describes the design of a new pressing device to produce composite rods. Computer modeling of mechanical properties of composite metal-polymer material was performed in the high-level CAD system DIGIMAT module MF. Micro-level modeling of the composite made it possible to establish the relationship between the percentage of inclusions and the upper yield strength of the material and the influence of the shape of the inclusions on the tensile strength of the designed material. The computational experiment results were verified with the results of the field experiment for the samples produced by the injection molding technology and the 3D printing technology.